2002
DOI: 10.1002/path.1040
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl‐x, Bcl‐2, Bax, and Bak in endarterectomy and atherectomy specimens

Abstract: The regulation of apoptosis in atherosclerosis is not completely defined. The aim of this study was to determine the expression of Bcl-2, Bcl-x, Bax, and Bak in relation to apoptosis in advanced atherosclerotic lesions. In atherectomy (15), endarterectomy (10), and control non-atherosclerotic segments of renal (2) and of coronary and carotid (5) arteries, the extent of apoptosis was determined using TdT dUTP nick end labelling (TUNEL) and nuclear morphology (karyorrhexis/pyknosis) and expression of apoptosis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 63 publications
5
32
0
Order By: Relevance
“…The alteration in the expression of Bcl-2 family protein appeared to be related to apoptosis of VSMCs in atherosclerosis. In the apoptotic cells of endarterectomy and atherectomy specimens, there was increased expression of pro-apoptotic Bax and Bak coupled with a paucity of Bcl-2 and lack of Bcl-X L [25]. Bax induced cyt c release from mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in the expression of Bcl-2 family protein appeared to be related to apoptosis of VSMCs in atherosclerosis. In the apoptotic cells of endarterectomy and atherectomy specimens, there was increased expression of pro-apoptotic Bax and Bak coupled with a paucity of Bcl-2 and lack of Bcl-X L [25]. Bax induced cyt c release from mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been closely associated with atherosclerosis because a higher apoptotic index has been observed in advanced atherosclerotic lesions compared with early ones (29,30,48). In the later stages of atherogenesis, up-regulated apoptosis in combination with impaired, cytoprotective autophagy in SMCs within the thin fibrous cap of lesions can promote plaque rupture, thrombosis, and subsequent myocardial infarction and stroke (1,3,4).…”
Section: Discussionmentioning
confidence: 99%
“…In a rabbit atherosclerotic model, increased levels of Bcl-X L , an anti-apoptotic member of the Bcl-2 family, have been found in the intima of early proliferative lesions and the down-regulation of Bcl-X L in neointima resulted in apoptosis of vascular cells and the regression of lesions (29). Likewise, higher Bcl-X L levels were observed in apoptosis-resistant cells of human advanced lesions compared with control specimens, and had a protective effect against apoptotic insults (30). Moreover, our prior work in transcript profiling of lesion-derived cell (LDC) apoptosis revealed that up-regulated expression of Bcl-X L is a major determinant of resistance to Fas-mediated apoptosis (31,32).…”
mentioning
confidence: 87%
“…10 -12 Atherosclerotic plaque apoptosis 6,8 is associated with predominant caspase-3 activation in SMCs 13 and macrophages. 7,12,14,15 Atherosclerotic SMCs and macrophages express pro-apoptotic regulators of mitochondrial integrity Bax and Bad, but they lack cytoprotective Bcl-xL and Bcl-2, 16,17 resulting in defective mitochondrial integrity and apoptosis. Moreover, the endogenous caspase inhibitor, cellular inhibitor of apoptosis (IAP) protein-2 (cIAP2) is thought to be expressed in atherosclerotic endothelial cells, 18 but these cells are prone to apoptosis in atherosclerosis.…”
mentioning
confidence: 99%